Effects of Levothyroxine and thyroid stimulating hormone on bone loss in patients with primary hypothyroidism - Mansoor Karimifar; Farah Esmaili; Amirhossein Salari; Ali Kachuei; Ziba Faragzadegan; Mozhgan Karimifar (Wolters Kluwer Medknow Publications, 2014)
Objective: Previous studies on bone mineral density (BMD) abnormalities associated with hypothyroidism are scarce and not conclusive. The effect of thyroid hormone therapy on BMD has shown mixed results. The aim of the present study was to determine the severities of osteoporosis in female patients with hypothyroidism in comparison to healthy women. Methods: This cross-sectional descriptive study was performed on 150 women aged over 50 years. Totally, 100 patients with primary hypothyroidism and 50 healthy subjects were enrolled in this study and divided into three groups. Group A, which consisted the patients who had been recently diagnosed with primary hypothyroidism. The second group of patients diagnosed with primary hypothyroidism for at least 2 years and was treated with levothyroxine (Group B). The third group of healthy individuals was selected as a control group (Group C). Blood samples were taken for the measurements of thyroid stimulating hormone (TSH), and bone densitometry was performed to determine the BMD reported as T-score in order to measure the severity of osteoporosis. T-score of the lumbar vertebra (L2-L4) and femoral neck were measured with dual energy X-ray absorptiometry and were compared between the three groups. Data were analyzed by SPSS using regression analysis and Mann-Whitney, Kruskal-Wallis, or analysis of variances statistical tests. The statistical significance was set at a P < 0.05. Findings: The average age of patients and baseline serum TSH levels in Group B was significantly different from the other two groups (P < 0.001). T-score of the lumbar spine (L2-L4) in Group B was significantly lower than the other groups (P = 0.01). The linear regression between serum TSH levels and BMD categories were not clearly associated. However, after removing the effect of the baseline TSH level in Group B, bone loss was significantly greater than the other two groups (P = 0.01). Conclusion: According to the present study, it seems that the treatment of hypothyroidism with thyroid hormones reduces both serum levels of TSH and bone density. Hence, proper control of this risk factor can be an effective way in prevention of osteoporosis.